Faktor-Faktor Yang Mempengaruhi Penerapan Konsep Ekonomi Syariah Dalam Kehidupan Masyarakat Wilayah Pesisir - Misdawita, Misdawita; Asrina, Putri; Rizwan, Muhammad (ITB AAS INDONESIA Surakarta, 2024)
The application of sharia principles in economics promises a more equitable and inclusive economic development. Implementing sharia economics in coastal areas provides a number of economic benefits for the community. Limited access to adequate resources and infrastructure can affect the community's ability to apply sharia economic principles. The purpose of this study was to determine what factors influence the application of the concept of sharia economics in coastal areas seen from internal and external factors. This study is a quantitative study. The respondents in this study were 300 people in the Meranti Islands who were already working. The data analysis technique used was multiple linear regression using the SEM-PLS model. The results of this study showed that the variables of education and skills, personality and motivation, social and economic, environment, and technology and information had a direct and significant effect on the application of the sharia concept in the coastal areas of the Meranti Islands. while the variables of policy and regulation did not have a direct and significant effect on the application of the sharia concept in the coastal areas of Meranti Regency.